Parental Motivation Toward Youth Residential Summer Camp Enrollment - Nack, Marcus A. (University of Wisconsin-Stevens Point, College of Natural Resources, 2018)
Residential youth summer camps offer a plethora of activities and experiences that can positively affect children’s lives. Children may want to attend summer camp for a variety of reasons, but ultimately the decision to enroll a child in summer camp is made by parents. Parental motivations toward youth residential summer camp enrollment are not fully understood, and this research seeks a better understanding of enrollment motivations by surveying parents during drop off procedures on the first day of summer camp. It is important for summer camps to understand why parents feel the need to enroll their children. With this information, summer camps can strategize approaches to give parents and children the best possible experiences. The objectives of this research were to 1) investigate parent motivations for enrolling children in summer camps, 2) better understand the expected outcomes parents have for their children at camps, 3) enable camps to adapt to meet the needs and expectations of parents, and 4) provide camps with information about their target audiences. Information was gathered from parents that enrolled their children at two residential youth summer camps in July and August 2017. This information revealed similar responses at both surveyed locations. Surveys also indicated that parents enrolled their children in summer camp because of the factors of time spent outside, camp activities, and child growth and development. These three enrollment factors had the strongest agreement responses, and tradition, cost, and childcare had the lowest agreement responses. Parents indicated that they had high intrinsic motivation (value-based motivation) and low extrinsic motivation (reward-based motivation) toward summer camp enrollment. Summer camps could use this information for strategic planning, summer camp marketing, and summer camp programming. From this research, recommendations were made about ways to appeal to parents and ultimately get more parents to enroll their children in summer camps.